Dialectical model of character and Franklin’s method - Mamali, Cătălin (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
The study analysis three personalities who generated selfrecords for a long period of time on their personality development and especially on character questions. The autobiographies** of Franklin, Gandhi and Thoreau’s Walden experiment are studied as paradigmatic modes of enhancing intentionally one’s own autonomy as a necessary condition to increase the personal ability to cope with major social conflicts for the sake of common good. The educational value of Franklin’s methods for character training is based on practical exercises carried with students.